Barack Obama´s Doctrine and His Approach towards Iran : Did Obama Act as a Wilsonian of the 21st Century? - Hlavsová, Aneta, 1989-; Eichler, Jan, 1952-; Druláková, Radka, 1973-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The dissertation´s main goal is to analyze to what degree Barack Obama acted as a Wilsonian in his overall foreign policy doctrine and specifically towards Iran. Through contrasting the 44th US president´s rhetoric and his actual foreign policy steps on certain topics, the dissertation aims to answer two central research questions:1. To what extent does Barack Obama´s foreign policy satisfy the criteria of Wilsonianism of the 21st century?2. Regarding the Iran Deal, to what extent does Barack Obama´s approach towards Iran satisfy the criteria of Wilsonianism of the 21st century? The case study of Iran deal was selected for its unprecedented international legitimacy given by the format of negotiations (the five permanent members of the UN Security Council plus Germany and Iran). The deal was sponsored by Obama´s vision of a world without nuclear weapons which was one of his original doctrinal ideals.For the study of Obama´s rhetoric, the method of in-vivo coding is applied to the president´s fifteen selected doctrinal speeches and documents, generating 7 clusters of testable codes representing his self-proclaimed foreign policy priorities. Those topics then subsequently undergo a newly developed test of Wilsonianism of the 21st century. The test was inspired by the theoretical contributions of Anne-Marie Slaughter, John Ikenberry, and Tony Smith and consists of four original questions which allows for the assessment of Obama´s Wilsonianism.The dissertation establishes Wilsonianism of the 21st century as a testable orientation of foreign policy and offers the tool to do so (i.e. the test of Wilsonianism of the 21st century can be reiterated in further research). Importantly, the dissertation confirms that Wilsonianism should remain an integral part of the study of international relations; the term has been misused and misunderstood many times in the past US foreign policy.
It is only through a properly developed framework of Wilsonianism, which would at the same time entail the realities of the 21st century politics, that international liberalism can become rehabilitated as valid foreign policy and this dissertation should serve as a step towards that. The research determines that Barack Obama majorly acted as a Wilsonian in his foreign policy. Most importantly, the assessment of the Wilsonian criteria showed that Obama did not attempt to impose democracy onto third states which had been a widespread feature of his predecessor´s foreign policy. Obama´s most prominent non-Wilsonian shortcomings relate to his unilateral demonstrations of US military power, notably through the employment of drone strikes. Towards Iran, the dissertation determines that Obama´s foreign policy was overwhelmingly Wilsonian (even more so than within his overall foreign policy doctrine). Therefore, the dissertation successfully answers both its research questions and thereby fulfills its main goals.
Vedoucí práce: Jan Eichler
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: mezinárodní politické vztahy [obor disert. práce]; disertace; dissertations